2003
DOI: 10.1046/j.1365-2494.2003.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of harvest date on the chemical composition and nutritive value of Cerastium holosteoides

Abstract: Cerastium holosteoides is a short‐lived plant often found in small proportions on dry and mesotropic semi‐natural, species‐rich grassland communities. To obtain more information about its nutritive value, two experiments on Arrhenatheretum elatioris grassland were carried out to examine the effect of harvest date on in vitro organic matter digestibility (IVOMD), neutral‐detergent fibre (NDF), acid‐detergent fibre (ADF), acid‐detergent lignin (ADL), estimated net energy for lactation (NEL) and crude protein (CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
5
5
0
Order By: Relevance
“…Advancing concentration may be attributed to decreased leaf to stem ratio with advancing plant age. Similar results were presented by Dong et al (2003), Dabo et al (1988), Kramberger and Klemen (2003) and Madakadze et al (1999).…”
Section: Discussionsupporting
confidence: 89%
“…Advancing concentration may be attributed to decreased leaf to stem ratio with advancing plant age. Similar results were presented by Dong et al (2003), Dabo et al (1988), Kramberger and Klemen (2003) and Madakadze et al (1999).…”
Section: Discussionsupporting
confidence: 89%
“…It was revealed in this study that there was no significant influence of time of harvest on mean ADF values of the shrubs, however, means ADF content was highest in plants harvested at 13 WAE. This observation was consistent with the findings of Kramberger and Klemencic (2003) and Sultan et al (2007) who reported increased ADF with maturity of grasses.…”
Section: Mean Proximate Compositionsupporting
confidence: 93%
“…CP content serves as an important indicator of fodder quality. In other studies, the CP content of Napier grass also decreased with maturity (Kramberger & Klemencic, 2003;Bayble, 2007;Sultan et al, 2007;Ansah et al, 2010;Jusoh et al, 2014). In the present study, despite the decline in CP content with increasing stage of maturity, the final concentration exceeded the minimum CP level (7.5%) required for rumen function (Jusoh et al, 2014).…”
Section: Discussionmentioning
confidence: 79%
“…Kramberger & Klemencic (2003), Bayble (2007) and Ansah et al (2010) reported that the DM content increased as Napier grass maturity increased. As expected, CP was highest in the early stage compared with the intermediate stage and late stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation